Fabrication of Nanoporous Alumina Ultrafiltration Membrane with Tunable Pore Size Using Block Copolymer Templates - Zhou, Chun; Segal-Peretz, Tamar; Oruc, Muhammed Enes; Suh, Hyo Seon; Wu, Guangpeng; Nealey, Paul F. (WILEY-V C H VERLAG GMBH, 2017)
Control over nanopore size and 3D structure is necessary to advance membrane performance in ubiquitous separation devices. Here, inorganic nanoporous membranes are fabricated by combining the assembly of cylinder-forming poly(styrene-block-methyl methacrylate) (PS-b-PMMA) block copolymer and sequential infiltration synthesis (SIS). A key advance relates to the use of PMMA majority block copolymer films and the optimization of thermal annealing temperature and substrate chemistry to achieve throughfilm vertical PS cylinders. The resulting morphology allows for direct fabrication of nanoporous AlOx by selective growth of Al2O3 in the PMMA matrix during the SIS process, followed by polymer removal using oxygen plasma. Control over the pore diameter is achieved by varying the number of Al2O3 growth cycles, leading to pore size reduction from 21 to 16 nm. 3D characterization, using scanning transmission electron microscopy tomography, reveals that the AlOx channels are continuous through the film and have a gradual increase in pore size with depth. Finally, the ultrafiltration performance of the fabricated AlOx membrane for protein separation as a function of protein size and charge is demonstrated.
Keywords: block copolymers; molecular separation; nanoporous alumina membrane; self-assembly; sequential infiltration synthesis; THIN-FILMS; DOMAIN ORIENTATION; FILTRATION; SEPARATION; DIFFUSION; PROTEINS; LAYER; Chemistry; Science & Technology - Other Topics; Materials Science; Physics